Analysis of the Compound Formulations of Conditional Speech Educational Tasks in the German Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Most of the analyzed textbooks are based on the communicative method of teaching the German language, and conditional communicative exercises predominate in them. In conditional communicative tasks, grammatical, lexical and phonetic forms are trained in the context of a simulated situation and assimilation occurs naturally, while in conditional speech exercises the forms are taken out of context, in isolation, in order to achieve automaticity in the use of these forms by students. The number of conditional speech exercises in the analyzed textbooks varies.